2020
DOI: 10.3390/bioengineering7010012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anabolic Effects of Reported Osteogenic Compounds on Human Mesenchymal Progenitor-Derived Osteoblasts

Abstract: There is variability in the reported effects of compounds on osteoblasts arising from differences in experimental design and choice of cell type/origin. This makes it difficult to discern a compound’s action outside its original study and compare efficacy between compounds. Here, we investigated five compounds frequently reported as anabolic for osteoblasts (17β-estradiol (oestrogen), icariin, lactoferrin, lithium chloride, and menaquinone-4 (MK-4)) on human mesenchymal progenitors to assess their potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Osteoblasts, specialized cells derived from mesenchymal stem cells (MSCs), are essential for bone formation and maintenance, and osteoblast dysfunction causes pathological fragility and diseases such as osteoporosis and periodontitis [ 3 ]. Rovert et al reported the anabolic effects of osteogenic compounds on human mesenchymal progenitor-derived osteoblasts and suggested the possibility of bone tissue engineering and bone diseases [ 4 ]. Anabolic treatments for osteoporosis increase the differentiation and maturation of osteoblast by altering bone metabolism [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoblasts, specialized cells derived from mesenchymal stem cells (MSCs), are essential for bone formation and maintenance, and osteoblast dysfunction causes pathological fragility and diseases such as osteoporosis and periodontitis [ 3 ]. Rovert et al reported the anabolic effects of osteogenic compounds on human mesenchymal progenitor-derived osteoblasts and suggested the possibility of bone tissue engineering and bone diseases [ 4 ]. Anabolic treatments for osteoporosis increase the differentiation and maturation of osteoblast by altering bone metabolism [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and collagen deposition were quantified on days 7 and 14 by alizarin red S (ARS) and direct red 80 (DR80), respectively, as previously reported Owen et al . [ 48 ] Briefly, the samples were rinsed twice in PBS then fixed by immersion in 3.7% formaldehyde for 30 min. Scaffolds were rinsed twice in diH 2 O, and then submerged in 1 w/v% ARS in diH 2 O for 30 min to stain for calcium.…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of a 2D cell culture into a microfluidic device has led to 3D approaches with sophisticated designs that mimic the mechanical and dynamic environments of native tissue. [ 226 ] Fabrication of complex, anisotropic, hierarchical macrostructures has been achieved by combining and integrating different technologies and materials. Bahmaee et al used a fabrication method based on a polymerized high‐internal‐phase emulsion (polyHIPE) to advance an osteogenesis‐on‐a‐chip device that incorporated a 3D environment and fluid shear stresses.…”
Section: Implementation Of Hierarchical Tissue Constructsmentioning
confidence: 99%